Pre-Clinical Assessment of Roflumilast Therapy in a Thoracic Model of Spinal Cord Injury - Carla S. Sousa; Rui Lima; Jorge R. Cibrão; Eduardo D. Gomes; Luís S. Fernandes; Tiffany S. Pinho; Deolinda Silva; Jonas Campos; António J. Salgado; Nuno A. Silva (MDPI AG, 2023)
The failure of axons to regenerate after a spinal cord injury (SCI) remains one of the greatest challenges in neuroscience. The initial mechanical trauma is followed by a secondary injury cascade, creating a hostile microenvironment, which not only is not permissive to regeneration but also leads to further damage. One of the most promising approaches for promoting axonal regeneration is to maintain the levels of cyclic adenosine monophosphate (cAMP), specifically by a phosphodiesterase-4 (PDE4) inhibitor expressed in neural tissues. Therefore, in our study, we evaluated the therapeutic effect of an FDA-approved PDE4 inhibitor, Roflumilast (Rof), in a thoracic contusion rat model. Results indicate that the treatment was effective in promoting functional recovery. Rof-treated animals showed improvements in both gross and fine motor function. Eight weeks post-injury, the animals significantly recovered by achieving occasional weight-supported plantar steps. Histological assessment revealed a significant decrease in cavity size, less reactive microglia, as well as higher axonal regeneration in treated animals. Molecular analysis revealed that IL-10 and IL-13 levels, as well as VEGF, were increased in the serum of Rof-treated animals. Overall, Roflumilast promotes functional recovery and supports neuroregeneration in a severe thoracic contusion injury model and may be important in SCI treatment.